ANALISIS PELAKSANAAN LELANG JAMINAN HAK TANGGUNGAN DALAM PENYELESAIAN KREDIT MACET PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK CABANG KENDARI - Bima Kurniawan Syamra (Kampus Akademik Publiser, 2024)
Implementation of the auction of collateralized land which is bound by mortgage rights. Even though it is not explicitly stated, material guarantees arise from an agreement. The guarantee rights law determines that basically the granting of mortgage rights is only possible if it is made in the form of an agreement that meets the requirements for the validity of the agreement. The research approach uses a statutory and conceptual approach. The data analysis used is qualitative analysis. The results of the research show that the implementation of the Parate Execution of Mortgage Rights on land is very difficult in practice due to inconsistencies between Article 6 UUHT and the General Explanation number 9 UUHT and the Explanation of Article 14 paragraphs (2) and (3) UUHT, which causes a distortion of meaning where The execution parate is equated with the grosse execution of the deed, namely the Court's fiat. Obstacles faced in the implementation of the auction of collateralized land which is bound by Mortgage Rights include: (a) inconsistencies in the material content in the UUHT; (2) Supreme Court Decision Number 3021/K/Pdt/1984 dated 30 January 1986, which stated that execution parate which was carried out directly at the Auction Office without going through the fiat of the Chairman of the District Court was an unlawful act; (3) Supreme Court Circular Letter (SEMA) Number 7 of 2012, which states that: Mortgage Auctions are carried out by creditors themselves through the Auction Office, if the auctioneer does not want to vacate the object being auctioned, it cannot be vacated based on Article 200 paragraph (11 ) HIR but must file a lawsuit.